2020
DOI: 10.3390/ma13214994
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Impact of Food Packaging Materials: A Review of Contemporary Development from Conventional Plastics to Polylactic Acid Based Materials

Abstract: Plastics have remained the material of choice, and after serving their intended purpose, a large proportion ends up in the environment where they persist for centuries. The packaging industry is the largest and growing consumer of synthetic plastics derived from fossil fuels. Food packaging plastics account for the bulk of plastic waste that are polluting the environment. Additionally, given the fact that petroleum reserves are finite and facing depletion, there is a need for the development of alternative mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
196
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 383 publications
(200 citation statements)
references
References 123 publications
0
196
0
4
Order By: Relevance
“…For example, polylactic acid polymer has been widely believed to easily biodegrade in landfills or home composts or even in aquatic environments. This is not true as the polymer does require an industrial composter and as such should be referred to as compostable [116][117][118][119][120].…”
Section: Biological Recyclingmentioning
confidence: 99%
“…For example, polylactic acid polymer has been widely believed to easily biodegrade in landfills or home composts or even in aquatic environments. This is not true as the polymer does require an industrial composter and as such should be referred to as compostable [116][117][118][119][120].…”
Section: Biological Recyclingmentioning
confidence: 99%
“…Specifically, despite constituting one of the global ecological challenges today (Lebreton and Andrady, 2019), plastic is still widely used by companies for product packaging (Kedzierski et al, 2020). The situation became even more severe thanks to the advent of home delivery and takeaway services (Ncube et al, 2020). In this context, Patrício Silva et al found that the COVID-19 pandemic is contributing to worldwide plastic pollution and precautionary measures challenged environmental sustainability (Patrício Silva et al, 2021).…”
Section: Lockdown Effects On Environmental Sustainabilitymentioning
confidence: 99%
“…Currently, plastic packaging waste is one of the biggest pollutants of the environment worldwide, thus the development of new food packaging materials with biodegradable or compostable properties is of great importance in the attempt to reduce the ecological impact [ 47 , 48 ]. In order to assess the compostable character of the manufactured green-based polymeric systems, the disintegration of the PLA-based mono and bilayer films was carried out under composting conditions.…”
Section: Resultsmentioning
confidence: 99%